2010
DOI: 10.1016/j.actbio.2010.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Microtopographical effects of natural scaffolding on cardiomyocyte function and arrhythmogenesis

Abstract: A natural myocardial patch for heart regeneration derived from porcine urinary bladder matrix (UBM) was previously reported to outperform synthetic materials (Dacron and expanded polytetrafluoroethylene (ePTFE)) used in current surgical treatments. UBM, an extracellular matrix prepared from urinary bladder, has intricate three-dimensional architecture with two distinct sides: the luminal side with a smoother surface relief; and the abluminal side with a fine mesh of nano- and microfibers. This study tested the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…UBM and its derivatives have been used successfully as extracellular matrix in external tissue construction [4850] and to support repair [2527]. First, our UBM characterization studies revealed an excellent biocompatibility with the brain since it did not elicit inflammatory responses greater than vehicle over the course of 3–4 weeks (data not shown).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…UBM and its derivatives have been used successfully as extracellular matrix in external tissue construction [4850] and to support repair [2527]. First, our UBM characterization studies revealed an excellent biocompatibility with the brain since it did not elicit inflammatory responses greater than vehicle over the course of 3–4 weeks (data not shown).…”
Section: Discussionmentioning
confidence: 78%
“…Coupled with the use of bioactive scaffolds to support extended survival and differentiation, stem cell transplantations have been successful in eliciting recovery from many injuries [2527]. The functions of bioactive scaffolds are no longer limited to rendering physical support for stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown the lack of an adverse immune response when an appropriately decellularized noncross-linked ECM biologic scaffold is placed within a xenogeneic recipient [Chen et al, 1999;Reddy et al, 2000;Brown et al, 2009;Daly et al, 2009]. Finally, it may be possible to use a 3-dimensional (3D) C-ECM patch seeded with stem cell-derived cardiomyocytes [Yang et al, 2008;Kamp and Lyons, 2009] to obtain an actively contracting patch as ECM in multiple in vitro investigations has been shown to support synchronously contractile cardiomyocytes [Ott et al, 2008;Eitan et al, 2010;Hata et al, 2010;Shah et al, 2010]. Additional studies are needed to assess the potential of C-ECM biologic scaffold material, but the possibility of using 3D C-ECM for the correction of CHD is promising.…”
Section: Discussionmentioning
confidence: 99%
“…Substrate topography can also influence cardiomyocyte properties. The effect of microtopography was studied using acellular porcine urinary bladder scaffold [145], which consisted of two distinct surfaces: a luminal side with smooth surface texture and an abluminal side with fine mesh network of nano-and microfibers. The results showed that the flat luminal surface had a higher density of neonatal cardiomyocytes with better contractile properties than the abuluminal surface.…”
Section: Topographymentioning
confidence: 99%